Luteolin and GroESL Modulate In Vitro Activity of NodD - Yeh, Kuo-Chen (American Society for Microbiology, 2002)
In the early stages of symbiosis between the soil bacterium Sinorhizobium meliloti and its leguminous host plant, alfalfa, bacterial nodulation (nod) genes are controlled by NodD1, NodD2, and NodD3, members of the LysR family of transcriptional regulators, in response to flavonoid and other inducers released by alfalfa. To gain an understanding of the biochemical aspects of this action, epitope-tagged recombinant NodD1 and NodD3 were overexpressed in Escherichia coli. The DNA binding properties of the purified recombinant NodD proteins were indistinguishable from those of NodD isolated from S. meliloti. In addition, the E. coli GroEL chaperonin copurified with the recombinant NodD proteins. In this study, we showed that NodD proteins are in vitro substrates of the GroESL chaperonin system and that their DNA binding activity is modulated by GroESL. This confirmed the earlier genetic implication that the GroESL chaperonin system is essential for the function of these regulators. Increased DNA binding activity by NodD1 in the presence of luteolin confirmed that NodD1 is involved in recognizing the plant signal during the early stages of symbiosis.